DAMPAK PENETAPAN HARGA TRANSFER TERHADAP PAJAK - Rajagukguk, Eska; Kesia, Tiori; Saribu, Ardin Dolok; Banjarnahor, Yesi; Simamora, Naomi; Simanullang, Paken Taras; Turnip , Asmida Rosari; Zebua, Irfan Zebua (Komunitas Manajemen Kompetitif, 2024)
Transfer price has an effectin tax avoidance, CompaniesCompanies try to find ways to divert their profits, instead of not paying their taxes, companies try to minimize their profits so that their taxes are also reduced.pay the tax, the company tries to minimize its profits so that the tax is also smaller.become smaller. That transfer pricing errors fell immediatelyafter the reforms, but then returned to its original level against the reformedtransfer pricing legislation was based on unfounded expectations of an increase and companies returned to manipulative practices.of improvement and that firms revert to their original transfer pricing manipulation practices once they are certain of the implications of the transfer pricing law.manipulation practices once they gain certainty about the implications of the new policy.of the new policy. Tax rate cuts will incentivizeincentivize transfer pricing due to more widespread profit shifting.widespread. This is because a higher withholding tax rate on royaltyroyalty payments encourage profit shifting through mispricing of goods.price of goods. Transfer Pricing can be done without being detrimental to tax authorities by using thetax authorities by using the OECD Method of setting a fair price.Translated with DeepL.com (free version)